International economic adjustment : small countries and the European monetary system - De Cecco, Marcello (New York : St. Martin's Press, 1983)
This is book comprise of studies on international economic adjustment with reference to small countries and the European Monetary System published in cooperation with the European University Institute, Florence. Topics covered includes: external shocks and adjustment policies in Finland 1973-80; the product link between exports and domestic demand: Sweden; symptoms of overvalued currency: the case of the Belgian Franc; Stabilisation policy in Austria; macroeconomic adjustment and exchange rate policy in middle-income countries: Greece, Portugal and Spain in the 1970s.
lje 18/09/2018
Loans
Keywords: Monetary policy, International; Foreign exchange rates; States, Small; Money; Europe